Examining the Moral and Ethical Expectations of the Nurse/Patient Relationship. - Pinckney, Michelle Y. (Journal of Chi Eta Phi Sorority (JOCEPS), 2021)
The therapeutic nurse-patient relationship must be focused solely on the care needs of the patient (Griffith, 2013). Nurses and patients develop a special bond based on trust, compassion and mutual respect (NSO, 2016). In the nurse-patient relationship, there is a discrepancy created by a nurse's positional power and a patient's vulnerability. The patient is considered vulnerable because of their dependence on the nurse's specialized knowledge and skills. In the dual relationship, nurses often used privileged information for their own benefit. Seven themes emerged from the non-research, nursing literature related to professional boundaries. These themes are: (1) Dual relations/role reversal, (2) Gifts and money, (3) Excessive self disclosure, (4) Secretive behavior, (5) Excessive attention/over involvement, (6) Sexual behavior and (7) Social media (Manfrin-Ledet, 2015).